Color stability of heat polymerized polymethyl methacrylate resin denture base after addition of high molecular nano chitosan - Ika Devi Adiana; Trimurni Abidin; Lasminda Syafiar (Dental Journal (Majalah Kedokteran Gigi), 2016)
Background: The addition of other ingredients to maintain color stability of heat polymerized polymethylmethacrylate is being developed. One of them is by adding high molecular nano chitosan. Purpose: This study aimed to determine the color stability of heat polymerized polymethyl methacrylate denture base resin after an addition of high molecular nano chitosan. Method: 30 sample pieces of acrylic plate (40x10x2 mm) were divied into 6 groups: control group and groups with the addition of chitosan nano gel percentages of 0.25, 0.50, 0.75, 1.0 and 1.50%. 2 ml chitosan nano gel was added into the mixture of acrylic resin with 23 g : 10 ml (P : L). After the mixture was inserted into a mold and then pressed and cured at 74oC for 120 minutes and then 100o C for 60 minutes. Acrylic plates were then released from the mold and finished. Color stability of acrylic resin were measured using UV-Vis Spectrophotometer and analyzed with a one way Anova. Result: The results showed significant differences in color stability after the addition of high molecular nano chitosan. The best color stability found in 1.0% the addition of chitosan nano gel group, the value was 0.07589 cm-1. Conclusion: The chitosan nano gel can be used to maintain color stability of heat polymerized polymethyl methacrylate denture base resin.